Injuries by events in combined events (decathlon and heptathlon) during 11 international outdoor athletics championships - Edouard, P.; Hollander, K. (Scandinavian Journal of Medicine & Science in Sports, 2025)
We aimed to determine whether some events carry a higher risk of injuries than others in combined events (decathlon and heptathlon) during international outdoor Athletics championships. A secondary aim was also to describe injury characteristics according to the different events. We conducted a total population study. During decathlon and heptathlon of 11 international outdoor Athletics championships from 2007 to 2024, in-competition injuries were collected by medical teams and local organizing committees. We performed descriptive analyses and calculated injury incidence rates by events. A total of 66 in-competition injuries and 2901 starts were reported for decathlon, and 67 in-competition injuries and 2063 starts for heptathlon. The proportion of injuries varied across events, with higher proportions in pole vault (19.7%) and high jump (18.2%) for decathlon, and in long jump (23.9%) and 800 m (16.4%) for heptathlon. The injury incidence rates varied across events, with higher rates in pole vault (46.3 (95% CI: 21.7 to 70.8)) and high jump (38.2 (95% CI: 17.0 to 59.4)) for decathlon, and in long jump (54.1 (95% CI: 28.3 to 79.8)) for heptathlon. The distribution of injury characteristics (i.e., location, type, mode of onset, severity) varied according to the events for decathlon and heptathlon. In conclusion, explosive jumping events had a higher risk of injuries than others within combined: pole vault and high jump for decathlon, and long jump for heptathlon. Injury characteristics varied according to the events. Our present study provides information that could help plan medical services during competitions of combined events and prepare athletes to face the injury challenge of combined events.